Comparative Analysis of Surgical Outcomes in Cardiac Myxoma Resection: Sternotomy Versus Right Mini-Thoracotomy - Elisa Mikus; Mariafrancesca Fiorentino; Diego Sangiorgi; Antonino Costantino; Simone Calvi; Elena Tenti; Elena Tremoli; Alberto Tripodi; Carlo Savini (Cardiovascular Innovations and Applications)
Despite increasing use of minimally invasive techniques, limited literature has described minithoracotomy for removal of left atrial masses, such as myxomas. This study was aimed at addressing this gap by analyzing more than a decade of experience at our center. Between January 2010 and May 2024, 116 patients underwent either right minithoracotomy or median sternotomy for left atrial myxoma resection. This retrospective study included 96 patients and excluded 20 patients receiving additional procedures. No prior sample size calculation was performed. The patients were divided into two groups: 36 (37.5%) who underwent right anterolateral minithoracotomy and 60 (62.5%) who underwent median sternotomy. Both groups had similar clinical characteristics (age P = 0.254, sex P = 0.274, BMI P = 0.128, and EuroSCORE II P = 0.470), tumor size (P = 0.596), and location (P = 0.954). No significant differences were found in intensive care unit or hospital length of stay, or major complications. The extracorporeal circulation time was shorter with sternotomy, despite similar cross-clamp times between techniques (P = 0.085). After inverse probability weighting, no significant differences were found in in-hospital mortality. Atrial fibrillation incidence was lower with minithoracotomy (P < 0.001). Minimally invasive resection of left atrial myxomas is as safe and effective as median sternotomy. Larger studies are required to validate these results.